Clinical characteristics of children with congenital Zika syndrome: a case series - Thais MASSETTI; Dafne HERRERO; Julliana ALENCAR; Talita SILVA; Cristina MORIYAMA; Flavia GEHRKE; James TONKS; Fernando FONSECA; Suzanna WATSON; Carlos MONTEIRO; Mariana VOOS (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: The congenital Zika syndrome involves structural brain changes, including ventriculomegaly, thin cerebral cortices, abnormal gyral pattern, cortical malformations, hypoplasia of the corpus callosum, myelination delay, subcortical diffuse calcifications, brainstem hypoplasia, and microcephaly in newborns. Objective: This study aimed to describe the clinical characteristics of children with congenital Zika syndrome; to compare the outcomes of infants infected in the first (1T, n=20) and second trimesters of pregnancy (2T, n=11); to investigate correlations between birth weight, birth and follow-up head circumference, birth gestational age, and gross motor scores. Methods: Participants were evaluated with Alberta Infant Motor Scale (AIMS) and part A of the Gross Motor Function Measure (GMFM-A). ANOVA compared head circumference, birth gestational age, birth weight, and gross motor performance of 1T and 2T. Results: The correlations were investigated by Pearson correlation coefficients. ANOVA showed differences in birth and follow-up head circumferences. Head circumference was smaller in 1T, compared to 2T. Motor performance was classified as below the fifth percentile in AIMS in all children and 1T showed lower scores in prone, sitting, and total AIMS score, compared to 2T. Children ranged from 8 to 78% on GMFM-A and there was a poorer motor performance of 1T. Nineteen children showed hypertonia, six showed normal tone and six showed hypotonia. Birth head circumference was correlated with AIMS prone postural control. Follow-up head circumference was correlated to prone, supine and total AIMS scores. Smaller head circumference at birth and follow-up denoted poorer postural control. Discussion: Children with congenital Zika syndrome showed microcephaly at birth and follow-up. Smaller head circumferences and poorer motor outcomes were observed in 1T. Infants showed poor visual and motor outcomes. Moderate positive correlations between birth and follow-up head circumference and gross motor function were found.